(untitled) (Colombia Medica, 2012)
Lymphocytopenia and CD4+ T lymphocytopenia can be associated with many bacterial, fungal, parasite and viral infections. They can also be found in autoimmune and neoplastic diseases, common variable immunodeficiency syndrome, physical, psychological and traumatic stress, malnutrition and immunosuppressive therapy. Besides, they can also be brought into relation, without a known cause, with idiopathic CD4+ T lymphocytopenia. Among viral infections, the Retrovirus, specially the human immunodeficiency virus, is the most frequently cause. However, many acute viral infections, including cytomegalovirus and Epstein Barr virus can be associated with transient lymphocytopenia and CD4+ T lymphocytopenia. As is well known, transient lymphocytopenia and CD4+ T lymphocytopenia are temporary and overcome when the disease improves. Nonetheless, severe CD4+ T Lymphocytopenia associated with chronic infections by human herpes virus has not been reported. We describe 6 cases of human immunodeficiency virus negative patients, with chronic cytomegalovirus and Epstein Barr virus infections and profound lymphocytopenia with clinical symptoms of cellular immunodeficiency. These patients improved rapidly with ganciclovir or valganciclovir treatment. We claim here that it is important to consider the chronic human herpes virus infection in the differential diagnosis of profoundly CD4+ T lymphocytopenia etiology, when human immunodeficiency virus is absent, in order to start effective treatment and to determine, in future studies, the impact of chronic human herpes virus infection in human beings’ health.